Valorization of raw glycerol for citric acid production by Yarrowia lipolytica yeast - Rywinska,Anita (Pontificia Universidad Católica de Valparaíso, 2010)
In the present report, citric acid production from raw glycerol in two fed-batch systems by acetate negative-mutants of Yarrowia lipolytica: Wratislavia 1.31 and Wratislavia AWG7 was compared. In the system, in which the total glycerol concentration was 200 g∙L-1, the substrate was added by pulsed additions, and in the other, in which the total glycerol concentration was 300 g∙L-1, the substrate was added at a constant feeding rate of 1.4 g∙h-1. Despite high citric acid concentrations (155.2 and 157.5 g∙L-1 with Y. lipolytica Wratislavia 1.31 and Y. lipolytica Wratislavia AWG7, respectively) obtained from 300 g∙L-1 of glycerol, the yield of citric acid was similar, i.e. about 0.6 g∙g-1. The volumetric citric acid productivity was markedly higher (1.05 and 0.94 g∙L-1h-1 with Y. lipolytica Wratislavia 1.31 and Y. lipolytica Wratislavia AWG7 strains, respectively) in the cultures containing 200 g∙L-1 of carbon source.